DETERMINANTS OF INDEPENDENT NURSING ACTIONS IN DAILY LIVING ACTIVITIES, CARING & SUPPORT, AND REHABILITATION IN INPATIENT WARDS OF THE GENERAL HOSPITAL OF DR. M. HAULUSSY AMBON - Hani Tuasikal; Ani Margawati; Luky Dwiantoro (Belitung Nursing Journal, 2017)
Background: Low independent nurse actions leads to poor health care quality. Therefore, understanding the factors affecting independent nursing action is necessity. Objectives: This study aims to analysis the independent nurse actions and its related and predicting factors. Methods: This study used a cross-sectional design with observational technique for data collection. There were 165 nurses recruited using simple random sampling in 14 inpatient wards of the General Hospital of dr. M. Haulussy Ambon, Indonesia. Spearman Rank Correlation and multiple regressions were used for data analysis. Results: Results of this study showed that there were significant relationships of age, gender, education, employment time, family burden, working experience, knowledge, workload, and nurse ability with independent nursing action with p-value <0.05. Nurse knowledge was the most dominant factor predicting independent nursing action with R-value 0.450. Conclusions: Independent nurse actions in daily living activities, caring & support, and rehabilitation were influenced by multiple factors such as nurse knowledge, ability, education and gender. Nurse knowledge is the most predicting factors affecting independent nursing action. Therefore, hospital and nurse managers need to well manage these predicting variables in order to improve independent nurse action that leads to the better quality of health service in the hospital.